Ovariectomy and subsequent treatment with estrogen receptor agonists tune the innate immune system of the hippocampus in middle-aged female rats. - Miklós Sárvári; Imre Kalló; Erik Hrabovszky; Norbert Solymosi; Zsolt Liposits (PLoS ONE, 2014)
The innate immune system including microglia has a major contribution to maintenance of the physiological functions of the hippocampus by permanent monitoring of the neural milieu and elimination of tissue-damaging threats. The hippocampus is vulnerable to age-related changes ranging from gene expression to network connectivity. The risk of hippocampal deterioration increases with the decline of gonadal hormone supply. To explore the impact of hormone milieu on the function of the innate immune system in middle-aged female rats, we compared mRNA expression in the hippocampus after gonadal hormone withdrawal, with or without subsequent estrogen replacement using estradiol and isotype-selective estrogen receptor (ER) agonists. Targeted profiling assessed the status of the innate immune system (macrophage-associated receptors, complement, inhibitory neuronal ligands), local estradiol synthesis (P450 aromatase) and estrogen reception (ER). Results established upregulation of macrophage-associated (Cd45, Iba1, Cd68, Cd11b, Cd18, Fcgr1a, Fcgr2b) and complement (C3, factor B, properdin) genes in response to ovariectomy. Ovariectomy upregulated Cd22 and downregulated semaphorin3A (Sema3a) expression, indicating altered neuronal regulation of microglia. Ovariectomy also led to downregulation of aromatase and upregulation of ERα gene. Of note, analogous changes were observed in the hippocampus of postmenopausal women. In ovariectomized rats, estradiol replacement attenuated Iba1, Cd11b, Fcgr1a, C3, increased mannose receptor Mrc1, Cd163 and reversed Sema3a expression. In contrast, reduced expression of aromatase was not reversed by estradiol. While the effects of ERα agonist closely resembled those of estradiol, ERβ agonist was also capable of attenuating the expression of several macrophage-associated and complement genes. These data together indicate that the innate immune system of the aging hippocampus is highly responsive to the gonadal hormone milieu. In ovariectomized female rats, estradiol replacement exerts potent immunomodulatory effects including attenuation of microglia sensitization, initiation of M2-like activation and modulation of complement expression by targeting hippocampal neurons and glial cells through ERα and ERβ.